Kōdō - its spiritual and game elements and its interrelations with the Japanese literary arts - Horiguchi, Satoru; Jung, Dinah (Journal of the Royal Asiatic Society, 2013)
In Japan, there are many kinds of dōs. The term has diverse and profound meanings, making it a challenge to define. Simply speaking, dō is a way for people to train the spirit by following specific practices, with the purpose of mastering life. Prominent examples of dōs include chadō / sadō (〔 茶 道 〕 so-called “tea ceremony”), kadō (〔 華 道 〕 so-called “flower arrangement”), shodō (calligraphy), and bushidō (the ethical code of the samurai). There are also sport practices such as jūdō (judo), kendō (kendo) and aikidō (aikido), all of which are also connected with the culture of dō.